The impact of minor trauma during pregnancy on maternal and neonatal outcomes: A tertiary centre experience - Shoshi Tenami; James Tankel; Alon D. Schwarz; Asher Ornoy; Sarah Goldberg; Sorina Grisaru-Granovsky; Yossi Freier Dror; Ofer Merin (Surgery in Practice and Science, 2023)
Introduction: The aim of this study was to evaluate the impact of minor trauma during pregnancy on maternal and fetal outcomes in patients managed in a tertiary setting. Materials and methods: A retrospective single centre case-controlled study was performed between 2005 and 2017 in a university affiliated tertiary obstetric and trauma centre. All pregnant women of 13–36 weeks gestation that presented to the department of emergency medicine with an Injury Severity Score of <9 were identified. Maternal and neonatal outcomes were compared with a control group of non-trauma pregnant women during the study at a ratio of 1:4. Variables found significant on univariate analysis were included in a multivariate regression analysis. Results: There were 388 patients allocated to the study group and 2528 to the control group. The groups were demographically similar, however trauma was more common amongst first-time mothers and those pregnant with twins. On univariate analysis, minor trauma was associated with lower gestation age at delivery, lower birth weight, more caesarean sections, lower Apgar scores at 1 and 5 min, longer neonatal hospital admissions and an increased incidence of neonatal intensive care admission. On multivariate analysis, minor trauma remained associated with an earlier gestational age at birth (OR 0.863, 95% CI 0.787-0.946, p = 0.002). Conclusion: Pregnant women who sustained minor trauma during pregnancy should be considered at high-risk of early labour.